Rescued Chondrogenesis of Mesenchymal Stem Cells under Interleukin 1 Challenge by Foamyviral Interleukin 1 Receptor Antagonist Gene Transfer - Armbruster, Nicole; Krieg, Jennifer; Weißenberger, Manuel; Scheller, Carsten; Steinert, Andre F. (Frontiers in Pharmacology, 2017)
Mesenchymal stem cells (MSCs) and their chondrogenic differentiation have been extensively investigated in vitro as MSCs provide an attractive source besides chondrocytes for cartilage repair therapies. Here we established prototype foamyviral vectors (FVV) that are derived from apathogenic parent viruses and are characterized by a broad host range and a favourable integration pattern into the cellular genome. As the inflammatory cytokine interleukin 1 beta (IL1β) is frequently present in diseased joints, the protective effects of FVV expressing the human interleukin 1 receptor antagonist protein (IL1RA) were studied in an established in vitro model (aggregate culture system) of chondrogenesis in the presence of IL1β. We generated different recombinant foamyviral vectors (FVVs) encoding enhanced green fluorescent protein (EGFP) or IL1RA and examined their transduction efficiencies and transgene expression profiles using different cell lines and human primary mesenchymal stem cells (MSCs) derived from bone marrow-aspirates. Transgene expression was evaluated by fluorescence microscopy (EGFP), flow cytometry (EGFP) and ELISA (IL1RA). For evaluation of the functionality of the IL1RA transgene to block the inhibitory effects of IL1β on chondrogenesis of primary MSCs and an immortalized MSC cell line (TERT4 cells), the cells were maintained following transduction as aggregate cultures in standard chondrogenic media in the presence or absence of IL1β. After three weeks of culture, pellets were harvested and analyzed by histology and immunohistochemistry for chondrogenic phenotypes. The different FVV efficiently transduced cell lines as well as primary MSCs, thereby reaching high transgene expression levels in 6-well plates with levels of around 100 ng/ml IL1RA. MSC aggregate cultures which were maintained in chondrogenic media without IL1β supplementation revealed a chondrogenic phenotype by means of strong positive staining for collagen type II and matrix proteoglycan (Alcian blue). Addition of IL1β was inhibitory to chondrogenesis in untreated control pellets. In contrast, foamyviral mediated IL1RA expression rescued the chondrogenesis in pellets cultured in the presence of IL1β. Transduced MSC pellets reached thereby very high IL1RA transgene expression levels with a peak of 1087 ng/ml after day 7, followed by a decrease to 194 ng/ml after day 21, while IL1RA concentrations of controls were permanently... (see revised manuscript)